Quota Formula : Data Update and Further Considerations. (Policy Papers; Policy Paper ;, 2013)
The IMF staff has updated individual member country data for the variables used in the quota formula for the period 1999-2011; the tables also include the comparable value of each variable for the previous quota dataset, which was based on data covering the period 1998-2010. The information is presented in millions of SDRs (Table A1) and in percent of their respective global totals (Tables A2 and A3). A table showing calculated quota shares based on the quota formula is also included (Table A4). The current quota formula includes a GDP variable, which is a blend of GDP at market rates and GDP at purchasing power parity (PPP), openness, variability, and international reserves (see Box 1 in Reform of Quota and Voice in the International Monetary Fund-Draft Report of the Executive Board to the Board of Governors). Data sources and a description of the quota variables are discussed in Quota Formula - Data Update and Further Considerations - Statistical Appendix; IMF Policy Paper; June 2013. Download Quota Data: Updated IMF Quota Formula Variables - July 2013.